Preparation method and application of bimetallic selenide / three-dimensional carbon composite material

By adopting the preparation method of dual -metal selenium/three -dimensional carbon composite material, the problem of insufficient chemotherapy characteristics of the selenium -based sodium ion battery negative electrode material, realizing the capacity, stable structure and excellent circulation performance of high sodium storage, improving sodium sodium Overall performance of ion battery.

CN118507684BActive Publication Date: 2025-01-28TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410621300.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-01-28
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

The existing negative electrode materials of sodium selenium-ion battery have insufficient chemical kinetic characteristics, resulting in sharp deterioration of electrochemical performance, poor rate performance and faster capacity decline after circulation.

Method used

The preparation method of dual metal selenium/three -dimensional carbon composite material is used to synthesize the selenium -zinc/three -dimensional carbon composite material through the water heat method and carbonization and selenium heat treatment. , Improve the structural stability and reaction of the material.

Benefits of technology

A significant improvement of sodium storage capacity, alleviating volume strain, improving the stability and cycle performance of the electrochemical structure, ensuring the excellent performance of sodium ion batteries and high capacity maintenance rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118507684B_ABST
    Figure CN118507684B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bimetallic selenide / three-dimensional carbon composite material, belonging to the technical field of electrode materials. S1, prepare a graphene oxide aqueous solution, impregnate melamine foam, and freeze-dry after sufficient impregnation; S2, carbonize in a nitrogen atmosphere, wash and dry after heat preservation; S3, prepare Cu 2+ and Zn 2+ aqueous solution, take an equal volume of Cu 2+ and Zn 2+ Aqueous solution is used to impregnate the three-dimensional composite carbon; S4, placing it in a reactor for hydrothermal reaction, cooling it to room temperature after taking it out, cleaning it, centrifuging it, and vacuum drying it to obtain a precursor; S5, taking selenium powder and the precursor, placing them in a tube test furnace, and annealing them in an argon / hydrogen mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material. The present invention provides a preparation method and application of a bimetallic selenide / three-dimensional carbon composite material. The composite material has good electrochemical structure stability. The prepared composite material is used in a sodium ion battery, and the prepared electrode sheet has excellent cycle performance and excellent rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a preparation method and application of a bimetallic selenide / three-dimensional carbon composite material. Background Art

[0002] Transition metal selenides have become a research hotspot in the field of electrochemistry due to their inherent metallic properties, layered structure and high theoretical capacity. Compared with traditional sulfides and oxides, transition metal selenides have higher conductivity, larger ion insertion gap and weaker M-Se bond, so they have better reaction reversibility. However, the inherent low conductivity, the shuttle effect of polyselenides, and severe aggregation and pulverization will lead to a sharp deterioration of their electrochemical performance, poor rate performance, and rapid capacity decay after cycling.

[0003] At present, the strategies to solve the above problems mainly include: structural design, carbon modification, potential window adjustment and construction of heterogeneous structures. For example, Hou et al. proposed a simple spatial confinement synthesis method to encapsulate SnSe spheres in a N, Se dual-doped carbon network (SnSe@NSC) derived from polydopamine (PDA). The in-situ formed SnSe embedded in the carbon matrix can not only prevent the aggregation of SnSe and slow down the volume change during the sodium insertion / de-sodiumization process, but also improve the structural stability through the Se-C bond at the interface between SnSe and the external carbon shell, showing a higher discharge capacity. However, since the particle size of SnSe nanoparticles is about 50nm, the physical contact performance is reduced during the cycle, the carrier transport is hindered, and the cycle performance needs to be further improved. In response to the above problems, the present invention provides a preparation method and application of a bimetallic selenide / three-dimensional carbon composite material. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a bimetallic selenide / three-dimensional carbon composite material to solve the problem of insufficient chemical kinetic properties of existing selenium-based sodium ion battery negative electrode materials.

[0005] To achieve the above object, the present invention provides a method for preparing a bimetallic selenide / three-dimensional carbon composite material, comprising the following steps:

[0006] S1, preparing a certain concentration of graphene oxide aqueous solution, impregnating melamine foam, and freeze-drying after sufficient impregnation;

[0007] S2, carbonizing in a nitrogen atmosphere, keeping warm and then cleaning and drying;

[0008] S3, prepare a certain concentration of Cu 2+ and Zn 2+ aqueous solution, take an equal volume of Cu 2+ and Zn2+ aqueous solution, and then impregnating the three-dimensional composite carbon;

[0009] S4, placing the precursor in a reactor for hydrothermal reaction, taking it out and cooling it to room temperature, washing it, centrifuging it, and vacuum drying it to obtain the precursor;

[0010] S5. Take selenium powder and precursor, place them in a tube test furnace, and perform annealing treatment in an argon / hydrogen mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material.

[0011] Preferably, in step S1, the concentration of the graphene oxide aqueous solution is 2-5 mg / mL.

[0012] Preferably, in step S2, the carbonization heating rate is 2-5°C / min, the carbonization temperature is 600°C-900°C, and the holding time is 1.5-3h.

[0013] Preferably, in step S3, Cu 2+ and Zn 2+ The concentration of the aqueous solution is 0.1-0.3 mM; the volume is 40-60 mL.

[0014] Preferably, in step S3, Cu(NO3)2, CuCl2, Cu(Ac)2, Zn(NO3)2, ZnCl2 or Zn(Ac)2 metal salt is used to prepare Cu 2+ and Zn 2+ Aqueous solution.

[0015] Preferably, in step S4, the hydrothermal reaction temperature is 160-200° C., the hydrothermal reaction time is 16-24 h; the centrifugal speed is 6000-10000 r / min, and the centrifugal time is 5-10 min.

[0016] Preferably, in step S5, the mass ratio of selenium powder to precursor is 1:5-10.

[0017] Preferably, in step S5, the flow ratio of argon / hydrogen gas is 17:1; the annealing temperature is 350-500° C., and the annealing time is 1-3 hours.

[0018] The present invention also provides a bimetallic selenide / three-dimensional carbon composite material prepared by the above preparation method.

[0019] The present invention also provides application of the bimetallic selenide / three-dimensional carbon composite material in a sodium ion battery.

[0020] Therefore, the present invention provides a preparation method and application of a bimetallic selenide / three-dimensional carbon composite material, and the specific beneficial effects are as follows:

[0021] (1) The transition metal selenium-based composite material prepared by the present invention has a high sodium storage capacity.

[0022] The present invention introduces three-dimensional composite carbon into the composite material to provide sufficient nucleation sites for the synthesis of copper zinc selenide, which is beneficial to the formation of nano-scale copper zinc selenide and greatly increases the specific surface area of ​​the composite material (such as Figure 1 The composite material (electrode) disclosed in the present invention can improve the sodium storage capacity of the composite material. The reversible capacity of the battery made of the composite material (electrode) disclosed in the present invention can reach 585.9 mAh / g when the current density is 0.05 A / g.

[0023] (2) The composite material prepared by the present invention can alleviate the volume strain of copper zinc selenide during the electrochemical process.

[0024] The three-dimensional composite carbon can provide abundant electron transport channels and has a positive effect on the distribution of copper zinc selenide. The unique spatial structure of three-dimensional carbon provides abundant active sites and a stable electrochemical structure for ion adsorption / desorption and embedding / ejection. It can also alleviate the volume expansion of copper zinc selenide during the charging and discharging process, which uses conversion reaction as the main sodium storage mechanism.

[0025] (3) The composite material prepared by the present invention has good electrochemical structural stability, and the prepared electrode sheet has excellent cycle performance.

[0026] The reaction kinetics of electrode materials directly reflects their ion transport efficiency. The copper zinc selenide / three-dimensional carbon composite material combines the kinetic advantages of copper zinc selenide, carbon fiber, and graphene components. The introduction of carbon fiber expands the interlayer spacing of graphene, and the introduction of graphene increases the nucleation sites of copper zinc selenide. Through the structural regulation of the composite material, the carrier transport efficiency is improved, and the reaction reversibility of the composite material is improved, resulting in a sodium ion battery with excellent cycle performance. When the current density is 1.0A / g, the reversible capacity retention rate reaches 86.5% after 1,000 cycles.

[0027] (4) The composite material prepared by the present invention has good reaction reversibility, and the electrode sheet (battery) prepared by using the composite material has excellent rate performance.

[0028] Compared with single metal selenides, bimetallic selenides can improve the thermodynamic stability and ion extraction dynamics of materials through lattice distortion, and provide more abundant redox active centers, which accelerates the transport of ions / electrons and improves the specific capacity of composite electrode materials. It can be seen from the rate curve that at current densities of 0.05, 0.1, 0.3, 0.5, 0.8, 1.0, 3.0, and 5.0 A / g, the specific capacity of copper zinc selenide / three-dimensional carbon composite materials is as high as 585.9, 538.1, 499.6, 461.8, 430.9, 378.8, 269.8, and 122.6 mAh / g. And when returning to a low current density, the capacity is basically not attenuated, which once again shows that the obtained composite material has excellent reaction reversibility.

[0029] (5) The present invention combines the hydrothermal method with carbonization and selenization heat treatment to prepare the composite material, which has simple process steps, mild reaction conditions, easy control, and convenient implementation. The raw material cost used is low, and it is suitable for large-scale production.

[0030] The hydrothermal reaction used in the preparation process of the composite material can be completed in an ordinary forced air drying oven, and all heat treatment processes are medium and low temperature heating in a tubular furnace. The equipment is conventional and there are no harsh conditions. This provides the possibility for conventional chemical plants to have ton-level reactors and large-scale production. The base material in the composite material is carbon material, which guarantees its low cost and environmental friendliness. The transition metals copper and zinc are conventional non-strategic resource metals, which also creates favorable conditions for the large-scale production of the composite material.

[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM morphology image of the copper zinc selenide / three-dimensional carbon composite material prepared in Example 1 of the present invention;

[0033] Figure 2 This is the XPS spectrum of the copper zinc selenide / three-dimensional carbon composite material prepared in Example 1 of the present invention;

[0034] Figure 3 The thermogravimetric curves of the copper zinc selenide / three-dimensional carbon composite material and pure copper zinc selenide prepared in Example 1 of the present invention;

[0035] Figure 4 This is a constant current charge and discharge curve diagram of the sodium battery prepared in Example 1 of the present invention at a current density of 0.05A / g;

[0036] Figure 5 The constant current charge and discharge curves of the sodium battery prepared in Example 1 of the present invention at different current densities;

[0037] Figure 6 This is a rate performance curve of the sodium battery prepared in Example 1 of the present invention;

[0038] Figure 7 This is a cycle performance curve of the sodium battery prepared in Example 1 of the present invention;

[0039] Figure 8 This is a SEM morphology image of the copper zinc selenide / three-dimensional carbon composite material prepared in Example 2 of the present invention;

[0040] Fig. 9 This is a SEM morphology image of the copper zinc selenide / three-dimensional carbon composite material prepared in Example 3 of the present invention;

[0041] Fig.10 This is a SEM morphology image of the copper zinc selenide / three-dimensional carbon composite material prepared in Comparative Example 1 of the present invention;

[0042] Fig.11 This is a SEM morphology image of the copper zinc selenide / three-dimensional carbon composite material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0043] The present invention provides a method for preparing a bimetallic selenide / three-dimensional carbon composite material, comprising the following steps:

[0044] S1, preparing a certain concentration of graphene oxide aqueous solution, impregnating melamine foam, and freeze-drying after sufficient impregnation;

[0045] S2, carbonizing in a nitrogen atmosphere, keeping warm and then cleaning and drying;

[0046] S3, prepare a certain concentration of Cu 2+ and Zn 2+ aqueous solution, take an equal volume of Cu 2+ and Zn 2+ aqueous solution, and then impregnating the three-dimensional composite carbon;

[0047] S4, placing the precursor in a reactor for hydrothermal reaction, taking it out and cooling it to room temperature, washing it, centrifuging it, and vacuum drying it to obtain the precursor;

[0048] S5. Take selenium powder and precursor, place them in a tube test furnace, and perform annealing treatment in an argon / hydrogen mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material.

[0049] In the present invention, in step S1, the concentration of the graphene oxide aqueous solution is 2-5 mg / mL; preferably 2.7, 3.8, 4.2, 4.5 mg / mL. If the mass concentration of graphene oxide is too low, the graphene oxide loaded on the surface of the melamine foam fiber will be insufficient, and if the mass concentration of graphene oxide is too high, it will cause agglomeration during the subsequent carbonization process when the graphene oxide is reduced to graphene, thereby reducing the utilization rate of graphene.

[0050] In the present invention, in step S2, the carbonization heating rate is 2-5°C / min, and the carbonization temperature is 600°C-900°C, preferably 650, 700, 800, 850°C. Too low a carbonization temperature will result in incomplete carbonization of melamine, and too high a temperature will cause the collapse of the three-dimensional carbon fiber structure during the carbonization of melamine. Keep warm for 1.5-3h.

[0051] In the present invention, in step S3, Cu 2+ and Zn 2+The concentration of the aqueous solution is 0.1-0.3 mM; preferably 0.15, 0.2, 0.25 mM. Too low a concentration will result in insufficient precursor generation and low yield of the obtained material, while too high a concentration will result in excess metal ions, waste of materials, and increased process costs. The volume is 40-60 mL.

[0052] In the present invention, in step S4, the hydrothermal reaction temperature is 160-200° C., the hydrothermal reaction time is 16-24 h; the centrifugal speed is 6000-10000 r / min, and the centrifugal time is 5-10 min.

[0053] In the present invention, in step S5, the mass ratio of selenium powder to precursor is 1:5-10.

[0054] In the present invention, in step S5, the flow ratio of argon / hydrogen gas is 17:1; the annealing temperature is 350-500° C., and the annealing time is 1-3 hours.

[0055] The present invention also provides a copper zinc selenide / three-dimensional carbon composite material prepared by the above preparation method. The prepared composite material has the following characteristics:

[0056] (1) Size characteristics: Copper zinc selenide / three-dimensional carbon composite materials are micro-nano composite materials. The carbon fibers derived from melamine carbonization are micron-sized, graphene is a nano-sized carbonaceous material, and the copper zinc selenide synthesized in situ on the carbonaceous substrate is nano-sized. Micron materials can increase the rate performance of the electrode, and nanomaterials can provide more active sites, which enhances the reversibility of the electrochemical reaction of the material. In order to give full play to the electrochemical activity of copper zinc selenide, the content of the carbonaceous substrate is preferably controlled below 15%.

[0057] (2) Structural and performance characteristics: Transition metal selenides achieve energy storage through conversion reactions, so the volume strain is large during the electrochemical process. Three-dimensional carbon mainly achieves energy storage through ion adsorption / desorption, so its electrochemical stability is relatively excellent. After the two constituent unit materials are combined, the synergistic effect makes the composite material exhibit electrochemical characteristics of high capacity and long cycle performance.

[0058] (3) Cost characteristics: The main component of copper zinc selenide / three-dimensional carbon composite material is copper zinc selenide. Copper and zinc are conventional transition metals with high abundance in the earth's crust. Therefore, developing composite material related technologies is advantageous for improving the electrochemical properties of composite materials and reducing the cost of composite materials.

[0059] The present invention also provides an application of the bimetallic selenide / three-dimensional carbon composite material in a sodium ion battery, and the specific steps are as follows:

[0060] The copper zinc selenide / three-dimensional carbon composite material, conductive carbon black or carbon nanotubes and polyvinylidene fluoride are mixed in N-methylpyrrolidone at a mass ratio of 7-8.5:2-1:1-0.5, stirred for 0.2-1h, and stirred until uniform; the obtained uniform electrode slurry is coated on the copper foil, and the loading amount reaches 3-10 mg / cm 2 If the loading is too low, it will have no reference value for production, while if it is too high, the material near the current collector will not be able to fully exert its performance. Therefore, the loading should be within an appropriate range. After coating, place it in a vacuum drying oven and dry it at 60-90°C for 12-48 hours. Punch it into a circular electrode sheet with a diameter of 12mm (as a negative electrode) or the corresponding electrode sheet size of a card battery; finally, form a two-electrode system with sodium foil in a glove box. The battery assembly model is CR2025 button battery or the corresponding card battery.

[0061] The following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] This embodiment provides a method for preparing a copper zinc selenide / three-dimensional carbon composite material, which specifically includes the following steps:

[0064] S1. Prepare a graphene oxide aqueous solution with a mass concentration of 3 mg / mL, add an appropriate volume of melamine foam to immerse, freeze for 12 hours, and then dry for 12 hours after sufficient immersion.

[0065] S2. Carbonization was carried out in a nitrogen atmosphere at a carbonization heating rate of 3°C / min and a carbonization temperature of 800°C. After keeping the temperature for 2 hours, the product was cleaned three times with deionized water and then vacuum dried at 60°C for 24 hours.

[0066] S3, use CuCl2 and ZnCl2 to prepare 0.2mM Cu 2+ and Zn 2+ Take 30 mL of each aqueous solution to impregnate the three-dimensional composite carbon.

[0067] S4. Transfer to a reactor and carry out a hydrothermal reaction at 180°C. Keep warm for 20 hours and then take out, cool to room temperature, wash with deionized water and centrifuge three times at a speed of 8000 r / min for 5 minutes. Then vacuum dry at 60°C for 12 hours to obtain a precursor.

[0068] S5. Take selenium powder and precursor in a mass ratio of 1:10, place them in a tube test furnace, and anneal them for 2 hours in an argon / hydrogen (flow ratio 17:1) mixed gas at 400°C to obtain a copper zinc selenide / three-dimensional carbon composite material.

[0069] Table 1 is a table showing the element contents of copper, zinc, selenium and carbon in the copper zinc selenide / three-dimensional carbon composite material prepared in this example.

[0070] Table 1

[0071]

[0072] Figure 1 This is a SEM morphology image of the copper zinc selenide / three-dimensional carbon composite material prepared in this example, which shows that the copper zinc selenide nanospheres are relatively evenly dispersed in the three-dimensional carbon gaps, with a particle size of about 600 nm.

[0073] Figure 2 This is the XPS spectrum of the copper zinc selenide / three-dimensional carbon composite material prepared in this example. It can be seen from the figure that the copper zinc selenide / three-dimensional carbon composite material is successfully synthesized.

[0074] Figure 3 Thermogravimetric curves of the copper zinc selenide / three-dimensional carbon composite material and pure copper zinc selenide (the preparation process of the pure copper zinc selenide is: no composite carbon is involved in the whole process, and other parameters and operations are the same as in Example 1) prepared in this embodiment. It can be seen from the figure that the mass content of the three-dimensional composite carbon in the composite material is about 9.7%.

[0075] The prepared composite material was used for electrode preparation / battery assembly: copper zinc selenide / three-dimensional carbon composite material, conductive carbon black and polyvinylidene fluoride were mixed in N-methylpyrrolidone at a mass ratio of 7:2:1 and stirred for 0.5h. The obtained uniform electrode slurry was coated on copper foil with a loading of 3.5mg / cm 2 After preparation, it was dried in a vacuum drying oven at 60°C for 12 hours, punched into circular electrode sheets with a diameter of 12 mm, and matched with metallic sodium in a glove box to form a two-electrode battery system, model CR2025, with a voltage test range of 0.01 to 3V.

[0076] Figure 4 is the constant current charge and discharge curve of the battery in this embodiment when the current density is 0.05A / g, Figure 5 The constant current charge-discharge curves at 0.05, 0.1, 0.3, 0.5, 0.8, and 1.0 A / g are shown in the figure. Figure 4 and Figure 5 It can be seen that after the third cycle, the curves overlap and the performance begins to stabilize. This is due to the formation of the SEI film, and the charging and discharging platform of the material is approximately 0.95V.

[0077] Figure 6 This is the rate performance diagram of the battery in this embodiment. The results show that at current densities of 0.05, 0.1, 0.3, 0.5, 0.8, 1.0, 3.0, and 5.0 A / g, the reversible capacity can reach 585.9, 538.1, 499.6, 461.8, 430.9, 378.8, 269.8, and 122.6 mAh / g.

[0078] Figure 7 The cycle life of the battery in this example at a current density of 0.05 A / g is shown in Figure 1. After 1000 cycles, the capacity retention rate reaches 85.9%. It can be seen that the prepared electrode material / battery exhibits good cycle stability.

[0079] Example 2

[0080] This embodiment provides a method for preparing a copper zinc selenide / three-dimensional carbon composite material, which specifically includes the following steps:

[0081] S1. Prepare a graphene oxide aqueous solution with a mass concentration of 5 mg / mL, add an appropriate volume of melamine foam to immerse, and after sufficient immersion, freeze for 12 hours and then dry for 12 hours.

[0082] S2. Carbonization was carried out in a nitrogen atmosphere at a carbonization heating rate of 5°C / min and a carbonization temperature of 900°C. After keeping the temperature for 2.5 hours, the product was cleaned three times with deionized water and then vacuum dried at 60°C for 24 hours.

[0083] S3, use Cu(Ac)2 and Zn(Ac)2 to prepare 0.3mM Cu 2+ and Zn 2+ Take 30 mL of each aqueous solution to impregnate the three-dimensional composite carbon.

[0084] S4. Transfer to a reactor and carry out a hydrothermal reaction at 200°C. After keeping warm for 24 hours, take out, cool to room temperature, wash with deionized water and centrifuge three times at a speed of 9000 r / min for 8 minutes. Then, vacuum dry at 60°C for 12 hours to obtain a precursor.

[0085] S5. Take selenium powder and precursor in a mass ratio of 1:8, place them in a tube test furnace, and anneal them for 3 hours at 350° C. in an argon / hydrogen (flow ratio 17:1) mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material.

[0086] The prepared composite material was used for electrode preparation / battery assembly: copper zinc selenide / three-dimensional carbon composite material, conductive carbon black and polyvinylidene fluoride were mixed in N-methylpyrrolidone at a mass ratio of 8:1:1 and stirred for 0.5h. The obtained uniform electrode slurry was coated on copper foil with a loading of 6mg / cm2 After preparation, it was dried in a vacuum drying oven at 60°C for 12 hours, punched into circular electrode sheets with a diameter of 12 mm, and matched with metallic sodium in a glove box to form a two-electrode battery system, model CR2025, with a voltage test range of 0.01 to 3V.

[0087] Figure 8 This is a SEM morphology picture of the copper zinc selenide / three-dimensional carbon composite material prepared in this example. The picture shows that the morphology of the copper zinc selenide spheres is looser than that of Example 1, which is related to the temperature and time of the hydrothermal reaction.

[0088] When the mass ratio of copper zinc selenide / three-dimensional carbon composite material, conductive carbon black and polyvinylidene fluoride was adjusted from 7:2:1 to 8:1:1, the specific capacity retention rate of the battery was 70.1% after 1000 cycles.

[0089] The electrochemical performance of the composite material prepared in this embodiment is lower than that in embodiment 1, and the overall performance of the battery is reduced. The structural characteristics of the composite material determine that the carrier transport efficiency is not as good as that in embodiment 1. At the same time, the reduction in the proportion of the conductive agent leads to a decrease in the electron collection efficiency, which ultimately leads to a decrease in the battery cycle performance.

[0090] Example 3

[0091] This embodiment provides a method for preparing a copper zinc selenide / three-dimensional carbon composite material, which specifically includes the following steps:

[0092] S1. Prepare a graphene oxide aqueous solution with a mass concentration of 2.5 mg / mL, add an appropriate volume of melamine foam to immerse, and after sufficient immersion, freeze for 12 hours and then dry for 12 hours.

[0093] S2. Carbonization was carried out in a nitrogen atmosphere at a carbonization heating rate of 2°C / min and a carbonization temperature of 600°C. After keeping the temperature for 1.5 hours, the product was cleaned three times with deionized water and then vacuum dried at 60°C for 24 hours.

[0094] S3, use CuCl2 and ZnCl2 to prepare 0.1mM Cu 2+ and Zn 2+ Take 30 mL of each aqueous solution to impregnate the three-dimensional composite carbon.

[0095] S4. Transfer to a reactor and carry out a hydrothermal reaction at 160°C. After keeping warm for 16 hours, take out, cool to room temperature, wash with deionized water and centrifuge three times at a speed of 6000 r / min for 10 minutes. Then vacuum dry at 60°C for 12 hours to obtain a precursor.

[0096] S5. Take selenium powder and precursor in a mass ratio of 1:5, place them in a tube test furnace, and anneal them for 1-3 hours at 350° C. in an argon / hydrogen (flow ratio 17:1) mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material.

[0097] The prepared composite material was used for electrode preparation / battery assembly: copper zinc selenide / three-dimensional carbon composite material, conductive carbon black and polyvinylidene fluoride (mass ratio of 8.5:1.5:0.5) were mixed evenly in N-methylpyrrolidone and stirred for 0.5h. The obtained uniform electrode slurry was coated on copper foil with a loading of 3mg / cm 2 , in a vacuum drying oven, at 90°C, keep warm for 18 hours, punch out circular electrode sheets with a diameter of 12 mm, and form a two-electrode system with sodium metal in a glove box. The battery assembly model is CR2025 button battery, and the voltage test range is 0.01~3V.

[0098] Fig. 9 This is a SEM morphology of the copper zinc selenide / three-dimensional carbon composite material prepared in this embodiment. The figure shows that the dispersion of copper zinc selenide / three-dimensional carbon is not as good as that of Example 1 and Example 2, and is not well dispersed in the three-dimensional carbon voids. This is related to the insufficient amount of metal ions and the short reaction time. At a current density of 0.05A / g, the reversible capacity is 315.6mAh / g, and after 1000 cycles, the capacity retention rate is 56.7%.

[0099] The microstructure and distribution of copper zinc selenide, the main active material in the electrode material, directly affect the comprehensive performance of the electrode material. Since the process parameters are lower than those in Example 1, its electrochemical performance is relatively low. Due to the small amount of copper zinc selenide formed, the three-dimensional carbon content in the composite material is relatively high, and the reduction of active sites of the electrode material cannot be compensated after adjusting the electrode ingredient ratio, resulting in lower performance than in Example 1.

[0100] Comparative Example 1

[0101] This comparative example provides a method for preparing a copper zinc selenide / three-dimensional carbon composite material, which specifically comprises the following steps:

[0102] S1. Prepare 7 mg / mL graphene oxide aqueous solution, add and immerse an appropriate volume of melamine foam, and after sufficient immersion, freeze for 12 hours and then dry for 12 hours.

[0103] S2. Carbonization was carried out in a nitrogen atmosphere at a carbonization heating rate of 3°C / min and a carbonization temperature of 900°C for 3 hours. The mixture was cleaned with deionized water three times and then vacuum dried at 60°C for 24 hours.

[0104] S3, use CuCl2 and ZnCl2 to prepare 0.4mM Cu 2+ and Zn2+ 30 mL of aqueous solution was then used to impregnate the three-dimensional composite carbon.

[0105] S4. Transfer to a reactor and carry out a hydrothermal reaction at 200°C. After keeping warm for 24 hours, take out, cool to room temperature, wash with deionized water and centrifuge three times at a speed of 10,000 r / min for 10 minutes. Then, vacuum dry at 60°C for 12 hours to obtain a precursor.

[0106] S5. Take selenium powder and precursor in a mass ratio of 1:10, place them in a tube test furnace, and anneal them at 500°C for 3 hours with argon / hydrogen (flow ratio 17:1) mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material.

[0107] The prepared composite material was used for electrode preparation / battery assembly: copper zinc selenide / composite material, conductive carbon black and polyvinylidene fluoride (mass ratio of 7:2:1) were mixed evenly in N-methylpyrrolidone and stirred for 0.5h. The slurry was coated on copper foil with a loading of about 3mg / cm2, vacuum dried at 60℃ for 12h, and punched into circular electrode sheets with a diameter of 12mm. The two-electrode system battery was assembled with sodium metal in a glove box. The battery model was CR2025 button cell, and the voltage test range was 0.01~3V.

[0108] Fig.10 This is the SEM morphology of the copper zinc selenide / three-dimensional carbon composite material obtained in this comparative example. It can be seen in the figure that the copper zinc selenide is in a blocky state, and a nano-scale composite material with excellent structure cannot be obtained. Because the copper zinc selenide / three-dimensional carbon structure is not ideal, its intrinsic electrochemical performance is not fully exerted. At a current density of 0.05A / g, its specific capacity is only 289.1mAh / g.

[0109] Comparative Example 2

[0110] This comparative example provides a method for preparing a copper zinc selenide / three-dimensional carbon composite material, which specifically comprises the following steps:

[0111] S1. Prepare a 1.5 mg / mL graphene oxide aqueous solution, add it to immerse an appropriate volume of melamine foam, and after sufficient immersion, freeze it for 12 hours and then dry it for 12 hours.

[0112] S2. Carbonization was carried out in a nitrogen atmosphere at a carbonization heating rate of 4°C / min and a carbonization temperature of 800°C. After keeping the temperature for 1.5 hours, the product was cleaned three times with deionized water and then vacuum dried at 60°C for 24 hours.

[0113] S3, use CuCl2 and ZnCl2 to prepare 0.05mM Cu 2+ and Zn 2+ Take 30 mL of each aqueous solution to impregnate the three-dimensional composite carbon.

[0114] S4. Transfer to a reactor and carry out a hydrothermal reaction at 140°C. Keep warm for 16 hours and then take out, cool to room temperature, wash with deionized water and centrifuge three times at a speed of 8000 r / min for 5 minutes. Then vacuum dry at 60°C for 12 hours to obtain a precursor.

[0115] S5. Take selenium powder and precursor in a mass ratio of 1:3, place them in a tube test furnace, argon / hydrogen (flow ratio 17:1) mixed gas, 250°C, anneal for 1 hour, and obtain a copper zinc selenide / three-dimensional carbon composite material.

[0116] The prepared composite material was used for electrode preparation / battery assembly: copper zinc selenide / three-dimensional carbon composite material, conductive carbon black and polyvinylidene fluoride (mass ratio of 8:1:1) were mixed evenly in N-methylpyrrolidone and stirred for 0.5h. The obtained slurry was coated on copper foil with a loading of about 2mg / cm 2 , vacuum dried (60℃, 12h), punched into circular electrode sheets with a diameter of 12mm, and assembled with metal sodium foil in a glove box to form a two-electrode system battery model CR2025 button battery. The voltage test range was 0.01~3V. At a current density of 0.05A / g, its specific capacity was only 289.1mAh / g.

[0117] Fig.11 This is the SEM morphology of the copper zinc selenide / three-dimensional carbon composite material prepared in this comparative example. Due to the changes in the preparation process of the copper zinc selenide / three-dimensional carbon composite material, copper zinc selenide is used as the main electrode active substance. Due to insufficient metal ion source and insufficient processing time and temperature, the electrochemical performance of the composite material is reduced, resulting in a low final specific capacity of the battery.

[0118] Based on the above embodiments and comparative data, it can be seen that the morphology and structure of the copper zinc selenide / three-dimensional carbon composite material will directly affect its electrochemical application. It is not difficult to find from the comparative embodiments and comparative examples that to ensure the synergistic efficiency of copper zinc selenide and three-dimensional carbon, and the relatively uniform structure of the composite material; the amount of metal ions should not be too much or too little, and it is best to use CuCl2 and ZnCl2. The amount of raw materials affects the difficulty of process implementation and the possibility of large-scale production. Therefore, the amount of titanate and graphene should be within the scope of not excessive use, the temperature and time of the hydrothermal reaction should be sufficient to ensure the structure of the composite material, and the temperature and time of the annealing treatment should be sufficient to ensure that nickel doping is effective. The setting of process parameters directly determines the possibility of large-scale application of materials. Therefore, the mass concentration of the graphene oxide aqueous solution used in the present invention is 2-5 mg / mL, the carbonization temperature is 600-900° C., the gold ion concentration is 0.1-0.3 mM, the hydrothermal reaction temperature is 160-200° C., the hydrothermal time is 16-24 h, the selenization temperature is 350-500° C., and the selenization treatment time is 1-3 h.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a bimetallic selenide / three-dimensional carbon composite material, characterized in that: The following steps are involved: S1, preparing a certain concentration of graphene oxide aqueous solution, impregnating melamine foam, and freeze-drying after sufficient impregnation; S2, carbonizing in a nitrogen atmosphere, keeping warm and then cleaning and drying; S3, prepare a certain concentration of Cu 2+ and Zn 2+ aqueous solution, take an equal volume of Cu 2+ and Zn 2+ aqueous solution, and then impregnating the three-dimensional composite carbon; S4, placing the precursor in a reactor for hydrothermal reaction, taking it out and cooling it to room temperature, washing it, centrifuging it, and vacuum drying it to obtain the precursor; S5, taking selenium powder and precursor, placing them in a tube test furnace, and performing annealing treatment in an argon / hydrogen mixed gas to obtain a copper zinc selenide / three-dimensional carbon composite material; In step S1, the concentration of the graphene oxide aqueous solution is 2-5 mg / mL; In step S3, Cu 2+ and Zn 2+ The concentration of the aqueous solution is 0.1-0.3 mM; the volume is 40-60 mL; In step S4, the hydrothermal reaction temperature is 160-200°C, the hydrothermal reaction time is 16-24h; the centrifugal speed is 6000-10000r / min, and the centrifugal time is 5-10min; In step S5, the mass ratio of selenium powder to precursor is 1:5-10; In step S5, the flow ratio of argon / hydrogen gas is 17:1; the annealing temperature is 350-500° C., and the annealing time is 1-3 hours.

2. The method for preparing a bimetallic selenide / three-dimensional carbon composite material according to claim 1, characterized in that: In the step S2, the carbonization heating rate is 2-5°C / min, the carbonization temperature is 600°C-900°C, and the insulation time is 1.5-3h.

3. The method for preparing a bimetallic selenide / three-dimensional carbon composite material according to claim 1, characterized in that: In step S3, Cu(NO3)2, CuCl2, Cu(Ac)2, Zn(NO3)2, ZnCl2 or Zn(Ac)2 metal salt is used to prepare Cu 2+ and Zn 2+ Aqueous solution.

4. A bimetallic selenide / three-dimensional carbon composite material, characterized in that: The bimetallic selenide / three-dimensional carbon composite material is prepared by the preparation method described in any one of claims 1-3.

5. The bimetallic selenide / three-dimensional carbon composite material according to claim 4, characterized in that: The bimetallic selenide / three-dimensional carbon composite material is applied in sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of high-performance nickel-cobalt selenide / three-dimensional graphene / nickel foam binderless electrode material

    CN109524245A

  • Bimetal selenide carbon microsphere composite material as well as preparation method and application thereof

    CN113130865A